DIGITAL MARKETING IN ENHANCING BUSINESS COMPETITIVENESS AMONG UMKM (MICRO, SMALL, AND MEDIUM ENTERPRISES): A CASE STUDY IN THE CULINARY SECTOR - niken niken; farida hanum; Sri Mulyani (Universitas Dharmawangsa Medan, 2026)
This study aims to determine the implementation of digital marketing strategies and their contribution to improving business competitiveness for UMKM in the culinary sector in Medan City. Using a descriptive qualitative method with a case study approach, data was collected through in deptth interview, observations, and documentation of seven UMKM in the culinary sector. The results showed that all informants had implemented social media platforms (Instagram, TikTok, WhatsApp, and Facebook) in their marketing efforts, but the level of optimization varied. Two groups were identified : those with advanced digital implementation (consistency, creative content, paid advertising, QRIS, data analysis) and those with simple, inconsistent implementation. Digital marketing has been shown to increase competitiveness through expanding market reach, increasing brand awareness, and increasing sales volume. The main obstacles include limited time, knowledge of content creation, understanding of algorithms, and data analysis skills. This study recommends improving content consistency, capacity development through training, and synergy between stakeholders to support the optimization of UMKM digital marketing. Keywords : Digital Marketing, Competitiveness, UMKM, Culinary Sector, Social Media